The world in prismatic views proceedings of the Second Interdisciplinary CHESS Interactions Conference, Saskatoon, Saskatchewan, Canada, 17-20 September 2012 (World Scientific Pub. Co., 2014)
This is one of the few unique books that explicitly explores what the common methodologies are across disciplines that stretch from the humanities to the exact sciences. The goal is to compare and contrast the modes of thinking and methods of research of diverse disciplines to allow readers to explore the common threads and distinct features of approach to research. Contributed by world-renowned authors, and written at a non-specialist level, it is accessible even to senior undergraduates and graduate students in various disciplines
Keywords: Interdisciplinary research / Congresses; Konferenzschrift